Co-treatment of Waste From Steelmaking Processes: Steel Slag-Based Carbon Capture and Storage by Mineralization - Zhao, Qing; Chu, Xinyi; Mei, Xiaohui; Meng, Qingzhang; Li, Jingyu; Liu, Chengjun; Saxén, Henrik; Zevenhoven, Ron (Frontiers in Chemistry, 2020)
Iron and steel industry is an energy-intensive sector, and large amounts of wastes/ by-products are generated during the steelmaking process, such as CO2, metallurgical slag, and wastewater. Enhancing the development and deployment of treating wastes from the steelmaking process will be environment friendly and resource-saving. Capturing CO2 by steel slag (SS) via mineralization is regarded to be an excellent choice since the high basicity of the slag. In this paper, recent research on the steel slag-based carbon capture and storage (SS-CCS) by mineralization was summarized. Three routes of SS-CCS are compared being, direct gas-solid carbonation, direct aqueous carbonation, and indirect carbonation, respectively. Furthermore, the challenges and prospects of the further development of the SS-CCS were discussed.